Knowledge and Attitudes of Cannabidiol in Croatia among Students, Physicians, and Pharmacists - Ana Batinic; Ana Curkovic; Josipa Bukic; Irena Žuntar; Sendi Kuret; Bianka Mimica; Nina Kalajzic; Goran Dujic; Ljubica Glavaš-Obrovac; Ana Soldo; Andrijana Včeva; Zeljko Dujic; et al. (MDPI AG, 2023)
Due to cannabidiol's health benefits and absence of serious side effects, its use is constantly growing. This is a survey-based cross-sectional study that was conducted to determine Croatian pharmacists', physicians', and students' knowledge and attitudes about cannabidiol (CBD). Two questionnaires were created, one for students and the other for physicians and pharmacists. Our participants (in total 874: 473 students and 401 physicians and pharmacists) generally had positive attitudes towards CBD therapy as approximately 60% of them believe that CBD treatment is generally efficacious. Participants had positive attitudes toward the therapeutic value of CBD, especially pharmacists and pharmacy students (63.8% and 72.2%, respectively). Pharmacists were significantly more convinced that CBD could reduce the use of opioids prescribed for chronic pain (p < 0.05). Only 17.5% of students had read scientific papers about CBD, compared to a significantly higher percentage of physicians and pharmacists (43.0% and 47.8%, respectively) (p < 0.05). This study revealed a gap in knowledge regarding CBD, since 89.3% of pharmacists and physicians, as well as 84.8% of students, believe they need more education about CBD. We conclude that it is important to improve the educational curricula so that medical professionals can recommend CBD use to their patients when needed.